The black theological call for an extended global family in Toni Morrison`s "Paradise" - Łobodziec, Agnieszka (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Black theological considerations of human existence involve metaphors corresponding to the concept of family . The formation of a beloved extended family may require a redefinition of certain Christian doctrines, an attempt made by some of the characters depicted in Toni Morrison`s ?Paradise?.
Keywords: black theology; interfaith dialogue; religious patriarchy; global family